PENGARUH EKSTRAK KEMANGI (Ocimum sanctum) TERHADAP KEMAMPUAN BELAJAR DAN MEMORI: JUMLAH SARAF NITRERJIK DI SUBIKULUM HIPOKAMPUS TIKUS (Rattus norvegicus) - , MOCHAMMAD NOVA RADITYA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Degradation of cognitive ability such as memory and learning knows adays are increasing progressively increasing and occurs in various age groups, not only in old age but also at the productive age. Holy basil (Ocimum sanctum) is a known herb which can improve cognitive ability. Cognitive abilities are controlled by hippocampus. Hippocampus consist of 3 there are dentate gyrus, hippocampus proper, and subiculum. One of the indication of cognitive ability improvement can be evaluated from neurotransmitter, one of which is Nitric Oxide (NO). The aim of research was to determine the influence of holy basil extract agains of cognitive ability which is evaluated from the number of nitrergic neurons on subiculum. Nine male rats (Rattus norvegicus) 4 weeks of age used, 50-60 g from Unit Development of Animal Laboratory of UGM was used on tihs research. Extract of holy basil (40 mg/kg BW) was given every day per-oral. At 2, 6, and 8 weeks of treatment 3 rats were anaesthetized using ketamine and xylazine (100 mg/kg and 10 mg/kg), perfused intracardiacally by Nacl 0.9% continued with phosphate buffer formalin 10%. The brain was taked out and processed for cryostat section 20Î¼m, n stained by hematoxylin Eosin (HE) and Nicotinamide Adenine Dinucleotide Phosphate-Diaphorase (NADPH-d) method. Nitrergic neurons on subiculum has pyramidal shape which is have positive reaction of blue chromatic and the nucleus was not stained. The percentage of nitrergic neurons in 2, 6, and 8 weeks of treatment are 12,29%